Low back pain – etiology, diagnostic and treatment - Świerkot, Jerzy (Przewodnik Lekarza/Guide for GPs, 2006)
Low back pain is one of the most common reason for physician office visits. Increasing age is associated with a greater frequency of low back pain – 20% in all adult and up to 49% in population over 65 years. It is one of the most expensive medical problems considering its direct and indirect costs. 90% cause of low back pain are the mechanical reason, the remain 10% are systemic illness. Low back pain requires a detailed history and physical examination that will allow differentiation of the common causes of low back pain from the more serious uncommon causes. Sometimes after all the diagnostic procedures the cause of low back pain remains unknown. The treatment should be complex, including drug therapy, rehabilitation and education. Life-style modification should be considered to avoid the low back pain.